Pelaksanaan Perjanjian Dan Akibat Hukum Dari Sewa Menyewa Rumah Dinas Milik Pemerintah Kabupaten Timor Tengah Selatan Ditinjau Dari Kitab Undang-Undang Hukum Perdata - Sakeh, Fahry Fausi; Nubatonis, Orpa J; Dju Bire, Chatryen M (Law Faculty, Nusa Cendana University, 2024)
The purpose of this study is to determine the implementation and legal consequences of the official residence rental agreement owned by the South Central Timor Regency Government. The type of research used is Empirical Law research, the type of data used in this study is qualitative. The data used in the study is based on the relevance of the source data, namely primary and secondary data. The results of this study suggest that in the implementation of the official residence rental agreement there is no contract agreement between the occupant of the official residence as the tenant and the Regional Government as the owner of the official residence. The tenant of the official residence only gets a Regent's Decree without any other documents. In terms of the contract agreement between the 2 parties, the legal force is not strong because the basis for the lease is only the Regent's Decree. The Regent's Decree is not an agreement document, but the Regent's Decree is a state administrative document. The impact of the absence of a contract is that many residents of the official residence have many arrears